Schizophrenia: advances in pathophysiology, management, and precision medicine - Akira Sawa; Joshua Chiappelli; Olivia P Hamrah; Nicola G Cascella (BMJ, 2026)
Abstract Schizophrenia is a common and severe mental condition with onset usually in late adolescence and young adulthood. Schizophrenia is caused by a combination of multiple genetic and environmental factors with significant neurodevelopmental implications. Advances in the clinical management of schizophrenia include biological and non-biological treatments. Drug interventions can ameliorate positive symptoms and prevent the progression of disease due to relapses. Non-biological approaches such as psychosocial and cognitive interventions can help functional improvement, relapse prevention, and early stage psychosis management, and new interventions such as neuromodulation and digital health interventions are still under investigation. Despite these advances, novel therapeutic strategies, particularly drugs, are hampered by a biologically heterogeneous population of patients with schizophrenia, a condition defined only by clinical operational criteria. Reconsidering the construct of schizophrenia from the viewpoint of mechanism driven precision medicine will be important, with stratification of patients on the basis of their biological characteristics. The first step towards this goal is to accumulate objective biomarkers for schizophrenia. On the basis of the framework of precision medicine, further advancement in the management of schizophrenia is expected.